2014
DOI: 10.7205/milmed-d-13-00343
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy of Virtual Reality Distraction in the Reduction of Pain and Anxiety During Cystoscopy

Abstract: We concluded no benefit to VR distraction mitigating pain in male patients during cystoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 13 publications
(2 reference statements)
1
95
3
1
Order By: Relevance
“…Some successes have been reported in the use of VR in the treatment of acute pain as an adjunctive method for pain control [2-7]. Clinical studies exploring its use for chronic pain remain minimal [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…Some successes have been reported in the use of VR in the treatment of acute pain as an adjunctive method for pain control [2-7]. Clinical studies exploring its use for chronic pain remain minimal [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism has anecdotally proposed by other VR rehabilitation studies (Perry et al, 2014). Alternatively, VR systems have been used to distract attention from pain (Keefe et al, 2012;Guo et al, 2014;Walker et al, 2014;Wiederhold et al, 2014) and decrease negative emotions about pain (Herrero et al, 2014;Triberti et al, 2014;Garcia-Palacios et al, 2015). The VR environment itself might distract attention and thus decrease pain (Wiederhold et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…One study found that an amputee patient who perceived a vivid subjective experience of moving their phantom limb reportedly showed the bimanualcoupling effect during the BCT, although another patient without this experience did not show the coupling effect (Franz and Ramachandran, 1988). Alternatively, VR systems have been used to distract attention from pain (Keefe et al, 2012;Guo et al, 2014;Walker et al, 2014;Wiederhold et al, 2014) and decrease negative emotions about pain (Herrero et al, 2014;Triberti et al, 2014;Garcia-Palacios et al, 2015). A high OI associated with BCT performance would indicate vivid movement representations of the affected hand (drawing circles), independent of real movements.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of distraction techniques during flexible cystoscopy have had mixed results; background music during the procedure may reduce anxiety and pain, 18, 19 while a virtual-reality distraction intervention did not. 20 In addition to these peri-procedural interventions to reduce invasiveness, another focus for improving the patient experience should be on pre- and post-procedural counseling that addresses cancer recurrence, given our finding that concern about recurrence contributes substantially to patients’ anxiety and worry.…”
Section: Discussionmentioning
confidence: 99%